Do we need two hammers in our toolbox? An empirical note about the potential redundancy of measuring subjective quality of life - Otto R. F. Smith; Otto R. F. Smith; Otto R. F. Smith; Marit Knapstad; Leif Edvard Aarø (Frontiers in Public Health, 2025)
BackgroundScales for the measurement of subjective quality of life (SQoL) and psychological distress are often used as if they measure different underlying concepts. This assumption is addressed in the present study by examining the discriminant validity between a set of items measuring SQoL and both the 2-item version of the Patient Health Questionnaire (PHQ-2) and the 5-item version of the Hopkins Symptom Checklist (HSCL-5).MethodsThe present study is based on baseline data (n = 1,599) collected as part of the Students’ Psychological Health Over Time (SPOT) study, conducted among Norwegian university students. Data were examined by means of a bifactor analytical framework. The SQoL instrument was compared in separate analyses against the PHQ-2 and the HSCL-5.ResultsPsychometric indices derived from the bi-factor model suggested that the SQoL instrument and the PHQ-2/HSCL-5 were essentially unidimensional. The overlap between scales was further confirmed by the finding that the associations between PHQ-2/HSCL-5 and a set of baseline correlates were similar to associations between the SQoL instrument and the same set of correlates.ConclusionThe SQoL instrument and the PHQ-2/HSCL-5 measure similar aspects for Norwegian university students. Combined with evidence from other studies, our findings suggest that using the SQoL instrument in addition to the PHQ-2 or HSCL-5 may be redundant.